Compound Heterozygosity (554-589 del, C515-T Transition) in the Platelet Glycoprotein Ibα Gene in a Patient with a Severe Bleeding Tendency - Margaglione, Maurizio; D’Andrea, Giovanna; Grandone, Elvira; Brancaccio, Vincenzo; Amoriello, Aldo; Di Minno, Giovanni (Thrombosis and Haemostasis, 1999)
Giant platelets in the blood smear, absent in vitro platelet agglutination in response to ristocetin, and normal aggregation, ATP secretion and thromboxane B2 formation were found in a young patient with a life-long bleeding tendency. Ristocetin-induced von Willebrand factor binding to her platelets was less than 10% of normal. Flow cytometric analysis with monoclonal antibodies LJ-Ib-1, LJ-Ib-10, and LJ-P3 was consistent with the latter finding. SDS-PAGE analysis of solubilized platelets showed a marked reduction of the platelet glycoprotein (GP) Ibα. Genetic characterisation demonstrated that the patient and her father were heterozygous for a deletion of 36 nucleotides (positions 554-589) leading to a mutant GPIbμ (deletion of aminoacids from residue 169 to 180 and a Glu → Lys substitution at residue 181). In addition, a C → T transition at nucleotide 515 in the other allele of the GPIbα gene was found in the patient and in her mother that results in the substitution of alanine for valine in codon 156 (Bernard-Soulier type Bolzano). These variations occurred within the VI and VII leucine-rich repeats. The novel variant of Bernard-Soulier syndrome identified further suggests that the integrity of leucine-rich repeats is important for normal function of the GP Ib-IX-V receptor complex.